High availability of vegetables and fruit through government-funded school lunch is not reflected in 4th grade pupils’ intake - Cecilia Olsson; Agneta Hörnell; Maria Waling (Food & Nutrition Research, 2023)
Background: An increased intake of vegetable and fruit (VF) through school meals can contribute to the prevention of non-communicable diseases. Objective: The purpose of this study was to investigate what types of VF 4th grade pupils (10–11 years old) choose, how much they eat when they are given the opportunity to serve themselves from the daily vegetable buffet available at lunch, and whether this varies with socioeconomic background and gender. Design: A cross-sectional study design was used where pupils’ VF intake was measured during 5 days with a photographic method. In total, 196 pupils from nine public schools participated. Results: The results show that pupils on average ate less than one type of VF per day from the vegetable buffet. Girls, pupils with a higher socio-economic status (SES) and those with a more frequent VF intake at home, ate more types of VF per day from the vegetable buffet than their counterparts. The median intake of VF from the vegetable buffet was generally low, 20.4 g/day. The intake was two thirds higher for pupils with higher SES in comparison with pupils with lower SES; 25 g/day versus14 g/day (P = 0.001). No gender differences in grams per day of VF were identified (P = 0.123). Discussion: This study indicates that a well-stocked vegetable buffet as part of government-funded school lunch does not automatically contribute substantially to the recommended daily intake of VF among a sample of 4th grade pupils in a high-income country like Sweden. Conclusions: The results of the study can be interpreted as a missed opportunity to increase the intentional consumption of VF among pupils in a way that would have implications for public health as well as attenuating differences between socioeconomic groups.